Book review: the novel “Teluk Alaska” - Wajdi, Majid; Susanto, Budi; Yuniantari, Ni Putu Intan; Nirmala , Ni Kadek Wahyu Dian; Dewi, Ayu Putu Lina Puspita; Kumbhayoni, Putu Diah Keshy; Putri, Kiki Hermalia (Yayasan Mitra Persada Nusantara, 2023)
The general problem in this study is